2017
DOI: 10.1186/s12872-017-0669-0
|View full text |Cite
|
Sign up to set email alerts
|

The top tertile of hematocrit change during hospitalization is associated with lower risk of mortality in acute heart failure patients

Abstract: BackgroundHemoconcentration has been proposed as surrogate for changes in volume status among patients hospitalized with acute heart failure (AHF) and is associated with a favorable outcome. However, there is a dearth of research assessing the clinical outcomes of hospitalized patients with hemoconcentration, hemodilution and unchanged volume status.MethodsWe enrolled 510 consecutive patients hospitalized for AHF from April 2011 to July 2015. Hematocrit (HCT) levels were measured at admission and either at dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…On the contrary, multiple studies revealed the inverse relations. [ 9 ], 11 18 ,[ 19 20 ] Data analysis of 1180 and 1776 patients in two randomized double blinded prospective studies demonstrated that 2-month rehospitalization was less frequently observed in individuals showing HC plus good diuretic response. [ 18 ] Another study on 336 HF persons with EF â30% revealed that while HC defining as any increased level of Hb or hematocrit (Hct) or plasma protein from baseline to discharge time was associated with worsening of renal function, 6-month mortality had been significantly lower than subjects not showing HC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, multiple studies revealed the inverse relations. [ 9 ], 11 18 ,[ 19 20 ] Data analysis of 1180 and 1776 patients in two randomized double blinded prospective studies demonstrated that 2-month rehospitalization was less frequently observed in individuals showing HC plus good diuretic response. [ 18 ] Another study on 336 HF persons with EF â30% revealed that while HC defining as any increased level of Hb or hematocrit (Hct) or plasma protein from baseline to discharge time was associated with worsening of renal function, 6-month mortality had been significantly lower than subjects not showing HC.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, they found that persons with HC had a lower likelihood of death compared to HD (HR: 0.39, 95% CI = 0.24–0.63) and NC ones (HR: 0.54, 95% CI = 0.33–0.88). [ 11 ] The other study on 2357 enrolled acute HF patients in order to calculate all-cause mortality and readmission rate suggested that obtaining HC during hospitalization period was associated with lower occurrence of adverse clinical events (HR: 0.67, 95% CI = 0.56–0.79, P < 0.001). [ 20 ] One study done over 1969 individuals referring with acute HF plus mild to moderate kidney dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was analyzed as a continuous variable for total activates MET and MET in each activity. Hematocrit (%) and hemoglobin (g/dL), which may imply hemodilution ( 15 ), were acquired from blood collected during the MEC examination using methods described by the US Department of Health and Human Services.…”
Section: Methodsmentioning
confidence: 99%
“…These results demonstrated that hemodilution and uid retention are common in CHF, especially in those with lower BMI level (BMI < 30kg/m 2 ). Previous studies indicated a higher mortality rate in patients with hemodilution than in those with hemoconcentration in acute heart failure patients [15], while uid restriction could only improve signs and symptoms of chronic heart failure in patients in moderate to severe chronic heart failure [40] and aggressive uid removal positively affected survival [41]. In the present study, CHF with BMI ≥ 30kg/m 2 participants had higher hematocrit and hemoglobin concentration than BMI < 30kg/m 2 ones, indicating that obese CHF participants were less likely to develop hemodilution.…”
Section: Participants' Characteristics Between Chf and Non-chfmentioning
confidence: 96%